LANGUAGE ACQUISITION AND DEVELOPMENT IN CHILDREN WITH AUTISM SPECTRUM DISORDER - Ratnawati; Fahmi Rakhman (Indonesian Journal of Education Teaching and Learning (IJETL), 2021)
The main function of language is to communicate or interact with other people. There have been many studies conducting about the language, especially about the process of language acquisition as it is an interesting and impressive aspect to be discussed in human development. The process of language acquisition starts from newborns period until they are adults. Language acquisition process deals with children, of course its process is vary between a child and others, particularly in the children with exceptionality such as children Autism Spectrum Disorders (ASD) or other disorders. The occurrence of ASD in the world increases rapidly every year. Thus, it is very important to discuss about language in children with ASD. According to the data base sources, the special education system and treatment to help children with ASD in developing their language will be discussed further in this paper.